2020
DOI: 10.1002/hed.26429
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngocutaneous fistulas after total laryngectomy or pharyngolaryngectomy: Place of video‐fluoroscopic swallowing study

Abstract: Background: Specify place of video-fluoroscopic swallowing study (VFS) in the decision of oral refeeding after total pharyngolaryngectomy. Methods: At postoperative day 7, a blue dye testing was performed. If negative, a VFS was performed looking for a blind fistula. If this exam was negative, oral refeeding was started, but if a blind fistula was observed, cervical compression bandage was performed. Results: In 186 patients, a VFS was performed for 142 patients with negative blue dye testing. It was negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Van La Parra et al created a grading system to classify leaks radiographically, which might help to determine which PL portends a higher risk to turn into a PCF 17 . Carsuzaa et al suggested to perform a blue‐dye test before VFSS to detect PCF; however, this did not appear useful in our series as only two patients out of 248 had a PCF at the time of initial VFSS 14 …”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Van La Parra et al created a grading system to classify leaks radiographically, which might help to determine which PL portends a higher risk to turn into a PCF 17 . Carsuzaa et al suggested to perform a blue‐dye test before VFSS to detect PCF; however, this did not appear useful in our series as only two patients out of 248 had a PCF at the time of initial VFSS 14 …”
Section: Discussionmentioning
confidence: 86%
“…17 Carsuzaa et al suggested to perform a blue-dye test before VFSS to detect PCF; however, this did not appear useful in our series as only two patients out of 248 had a PCF at the time of initial VFSS. 14 The overall diagnostic performance of VFSS in the detection of PL after TL seems acceptable (Table 4). However, two retrospective studies warned against the poor diagnostic performance of VFSS in the salvage setting.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Overall, our data correspond to the lower end of reported rates for these complications, despite broad inclusion criteria for each. In the literature, the incidence of complications varies from 4.6 per cent to 48.8 per cent 29 for fistula, and from 11 per cent to 60 per cent for strictures. 30,31 In addition, pharyngeal resection is associated with a variety of complications and significant overall morbidity.…”
Section: Discussionmentioning
confidence: 99%